The role of discourse in the constitution of radiographic knowledge: a critical realist account,Role of language in the constitution of radiographic knowledge: a critical realistic account - Wright, Jennifer Lynne (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2008)
The ways in which knowledge is constituted in Higher Education in South Africa today needs to take into account the historical diversity of learners' academic and literacy competencies. The thesis begins by considering the ways in which, historically, many learners in Higher Education have been under prepared for the challenges of studying complex disciplines through the medium of English, which is often their second or third additional language. It also considers the sometimes inappropriate response of Higher Education to the plight of these learners and the present and potential role of language specialists working in collaboration with disciplinary specialists to support these learners. In this ethnographic research, I use an ontological metatheory, critical realism, as my analytical lens. Critical realism is an appropriate analytical lens for exploring and gaining insight into the possible causal mechanisms that generate the stratified and often inscrutable nature of social reality, including the role of language and discourse in education. I employ a case study design to explore the role of discourse in lecturers and clinical radiographers' constitution of the knowledge of entry level Radiography learners at the Groote Schuur campus of Cape Peninsula University of Technology (CPUT). Taking discourse as my unit of analysis, I develop a model of knowledge constitution based on a Hallidayan framework (1978). This model comprises two contexts of culture (Higher Education and Health Care) within which are embedded two contexts of situation (the university classroom and a clinical radiography workplace). In these contexts, I focus on how lecturers and clinical radiographers constitute radiographic knowledge through the field, tenor and mode of their discourse. My research sheds light on learners' construal of various aspects of this process of knowledge constitution, and I consider implications for Radiography teaching and learning. I conclude that, because of the dual contexts in which the learners' knowledge is constituted, literacy requirements in the two contexts are quite different. For this reason, learners may often be unmotivated to enhance their literacies, particularly in reading and writing; yet, in the interests of the future growth of the profession, the latter will be required of them as practitioners who conduct research and publish. I argue that the real empowerment of Radiography learners thus lies in their lecturers' agency: there is a need for them to implement certain practices that will shape the learners' identity, not only as clinical practitioners, but as researchers and writers. In doing this, they will ensure that the learners' potential is realised and they have the capacity to make meaningful contributions to the growth of the future radiography profession.
Keywords: Education, Higher -- South Africa; Universities and colleges -- South Africa; English language -- Study and teaching (Higher) -- South Africa; Language and education; Discourse analysis; Radiography -- Study and teaching